Pengaruh Promosi Dan Physical Evidence Terhadap Keputusan Pembelian Pada Coffee Swic Of Paradise Kabupaten Bandung - Trianingsih, Komang Reni; Jamiat, Nuslih (eProceedings of Management, 2024)
The development of times in the current era of globalization has a huge impact on many fields that are increasinglyrapid in the business sector in Indonesia. One of them is the culinary business which is currently on the rise, namelyCoffee shop. One of the Coffee business actors in Bandung Regency, namely Coffee Swic of Paradise, is a coffee shopthat provides a variety of menus ranging from coffee or non-coffee menus to food that serves western and orientalstyles. In the sales of Coffee Swic of Paradise Bandung Regency, There are problems with inappropriate purchasingdecisions, so that sales targets are not achieved. Based on the results of the pre-survey of respondents, purchasingdecisions were influenced by promotions and physical evidence. This research aims to find out how much influencepromotions and physical evidence have on purchasing decisions at Coffee Swic of Paradise, Bandung Regency. Themethod used in this research is quantitative method with descriptive research type. The population used in this studyis the people of Bandung Regency who have visited Coffee Swic of Paradise Bandung Regency and respondents whohave made purchases at Coffee Swic of Paradise Bandung Regency at least 2 times with a sample of 160 respondents.The sampling used in this study was nonprobability sampling with purposive sampling technique. Based on the resultsof research using descriptive analysis with the help of SPSS 26 software for Windows, the Promotion and PhysicalEvidence variables are included in the good category and have a significant influence both simultaneously andpartially on purchasing decision at Coffee Swic of Paradise Bandung Regency.Keywords-promotion, physical evidence, purchase decision